Determinants of Millenial’s Intention to Participate in Digital Training - Abdul Kader Jailani, Sri Fatiany; Suzila Kassim, Erne (International Journal of Psychosocial Rehabilitation, 2019)
This paper seeks to identify the determinants of millennials’s intention to participate in digital training. The determinants were measured as entertainment gamification, motivational gamification, perceived usefulness, and perceived ease of use. A self-administered questionnaire was utilized for data collection, and data from 127 millenials was used. The results of PLS-SEM suggest entertainment gamification, motivational gamification, perceived usefulness, and perceived ease of use are significantly related to intention to participate in digital training. In fact, perceived ease of use was found to have the strongest linkage with the intention, followed by perceived usefulness and motivational gamification. The findings suggest organizations should pay attention to digital training investment and future research to focus on the digital training design.